Study the microstructure and mechanical properties of dissimilar friction stir spot welding of carbon steel 1006 to aluminum alloy aa2024-t3 - Tareq Abdullah, Isam; Khalil Ibrahim, Zaman; Ibrahim Razooqi, Ahmed (International Journal of Engineering and Technology, 2018)
Friction stir spot welding-FSSW has been suggested as effectual process to welding difficult materials such as dissimilar materials and thin sheet of metal alloys. In this study, using dissimilar materials were welded carbon steel-1006 on upper plate and aluminum alloy AA2024-T3 on lower plate. Macrostructure, micro-structural analysis and mechanical properties of the joints are done. The effect of penetration depth, dwell time and spindle speed on tensile shear load are investigated with invariable of other parameter during welding process. The maximum tensile shear load (3.31KN) was occurred when using 0.4mm of penetration depth, 10 sec of dwell time and 1400 rpm of spindle speed. Also, two type of failure shape was observed interfacial fracture of carbon steel sheet and pull-out fracture of AA2024-T3 sheet.Â Â Â